Trend of critical thinking skill researches in mathematics education in Scopus database across Indonesia: From research design to data analysis - Siahaan, Erika Yohanna Seventina; Muhammad, Ilham; Dasari, Dadan (SAINTIS Publishing, 2023)
The ability to think critically is one of the goals of education in Indonesia by emphasizing students' ability to think and act uncritically for every element of life. This study uses content analysis of 28 articles published in the Scopus database from 2013 to 2023 regarding students' critical thinking skills in mathematics education as the main focus. This research reveals that 2020 saw a very significant increase in publications in Q2 and Q3. The Indonesian Education University is an institution that has a lot of cooperative relations with other institutions in this field. Among these publications, real material analysis is the most researched topic with RME as the most frequently used treatment. The dominant research design is quantitative. Tests and t-tests are the most commonly used data analysis instruments and techniques, respectively. There are various types of design, treatment, collection techniques and data analysis used, therefore future researchers are advised to choose the most appropriate method for conducting research.